The Strength and Target-Seeking Characteristics of the Automatic Stabilizers - Packer, Arnold H.; Ripley, Frank C. (Quarterly Journal of Economics, 1975)
A framework for analyzing stability, 314. — Estimates of the stabilizers in the U. S. economy, 316. — Target-seeking characteristics, 319.